The Capacity of Human Resources at the Bontang City DPRD Secretariat in Supporting the Legislative Function: An Analysis of Competencies and Bureaucratic Barriers - Mappaelo; Bambang Irawan; Saipul (GoAcademica Research & Publishing, 2026)
This study aims to examine how bureaucratic competence and institutional constraints influence the effectiveness of legislative support provided by the Secretariat of the Regional House of Representatives of Bontang City in carrying out its legislative function. The study employs a qualitative approach with a case study design to capture empirical conditions related to the technical, managerial, and behavioral capacities of public officials, as well as structural and procedural obstacles within the organizational environment. The findings indicate that disparities in staff competencies, low educational qualifications, ineffective internal coordination, and rigid administrative procedures have hindered the timely provision of legislative support. In addition, limited technological facilities and a reactive work culture have reduced organizational responsiveness. The study concludes that enhancing the effectiveness of legislative support requires integrated efforts through strengthening staff capacity, simplifying bureaucratic procedures, improving coordination mechanisms, and reforming organizational work culture within the Secretariat of the Regional House of Representatives of Bontang City.